HUBUNGAN MINAT DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS - My Ismail; Paustina Ngali Mahuze (Yayasan Nusantara Hasana Berdikari, 2023)
This research is a quantitative research that aims to find out and analyze: (1). The relationship between interest and economic social studies learning outcomes in public high schools in West Muna district, (2) the relationship between discipline and economic social studies learning outcomes in public high schools in West Muna district, (3) the relationship between learning interest and learning discipline together with learning outcomes of Social Sciences Economics Class XI IPS students of State Senior High Schools in West Muna Regency.